Associations between theory of mind and clinical symptoms in recent onset schizophrenia spectrum disorders - Cayouette, Audrey; Thibaudeau, Élisabeth; Cellard, Caroline; Roy, Marc-André; Achim, Amélie M. (Frontiers in Psychiatry, 2023)
Introduction People with schizophrenia often present with Theory of mind (ToM) deficits, and the link between these deficits and clinical symptoms remains to be refined, for instance through the use of more recent assessment methods. The objective of this study was to examine the associations between a psychometrically sound ToM task and the clinical symptoms of schizophrenia as measured with the five dimensions of the Positive and Negative Syndrome Scale (PANSS) namely positive, negative, cognitive/disorganization, depression/anxiety and excitability/hostility, while controlling for non-social cognitive abilities. Methods Seventy participants with recent-onset schizophrenia spectrum disorders (SSD) were assessed for ToM using the Combined stories task (COST) and for clinical symptoms using the PANSS. Results The results revealed significant correlations between ToM and the positive (r = −0.292, p = 0.015) and cognitive/disorganization (r = −0.480, p < 0.001) dimensions when controlling for non-social cognitive abilities. In contrast, the negative symptoms dimension was only significantly correlated with ToM when non-social cognitive abilities were not controlled for (r = −0.278, p = 0.020). Discussion Very few prior studies used the five-dimensions of the PANSS to examine the link with ToM and this study is the first to rely on the COST, which includes a non-social control condition. This study highlights the importance of taking non-social cognitive abilities into account when considering the relationship between ToM and symptoms.